Ethnographic narrative on teaching Portuguese as a Host Language for a Syrian refugee family in Brazil - Bergamasco, Gabriele; Dornelles, Clara (Universidade Estadual Paulista, 2021)
When arriving in the new country, refugees are faced with the challenge of learning an often-unknown language and becoming familiar with the new culture(s). This was the case of the Syrian refugee family participating in this research. Our study took an ethnographic perspective (FONSECA, 1999) and aimed, from journals written by the researcher, to register our approach to the family in the context of teaching Portuguese. Furthermore, we describe the institutional construction of a welcoming and teacher formation proposal through the teaching of Portuguese by teachers of the Languages without Borders Program - Portuguese as an Additional Language (IsF-PLA), of the Federal University of Pampa. It was possible to identify that teaching practices were changing as there was an approximation of the family and consequent planning according to the linguistic-cultural needs of the students, from the perspective of teaching Portuguese as a host language (GROSSO, 2010).